2014
DOI: 10.2196/jmir.3133
|View full text |Cite
|
Sign up to set email alerts
|

mHealth and Mobile Medical Apps: A Framework to Assess Risk and Promote Safer Use

Abstract: The use of mobile medical apps by clinicians and others has grown considerably since the introduction of mobile phones. Medical apps offer clinicians the ability to access medical knowledge and patient data at the point of care, but several studies have highlighted apps that could compromise patient safety and are potentially dangerous. This article identifies a range of different kinds of risks that medical apps can contribute to and important contextual variables that can modify these risks. We have also dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
231
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(241 citation statements)
references
References 25 publications
7
231
0
3
Order By: Relevance
“…Cost alone is not indicative of quality or effectiveness. As mobile device use becomes ubiquitous, practitioners will need to be better informed regarding the design and content of mobile health apps so they can assess for themselves their value and worth for clinical practice (Lewis and Wyatt, 2014). Currently, there is limited evidence and guidance to support these decisions (Mohr et al, 2013).…”
Section: Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Cost alone is not indicative of quality or effectiveness. As mobile device use becomes ubiquitous, practitioners will need to be better informed regarding the design and content of mobile health apps so they can assess for themselves their value and worth for clinical practice (Lewis and Wyatt, 2014). Currently, there is limited evidence and guidance to support these decisions (Mohr et al, 2013).…”
Section: Qualitymentioning
confidence: 99%
“…Stoyanov et al (2015) have developed a Mobile Apps Rating Scale (MARS) that rates apps according to their engagement, functionality, aesthetics, information quality and subjective quality (Baumel and Muench, 2016). Other authors have recommended the development of risk assessment frameworks to support practitioners (Lewis and Wyatt, 2014). However, most of these endeavors are focused on product evaluation and provide little support to help the practitioner wishing to evaluate an app's effectiveness within the context of a clinical intervention (Baumel and Muench, 2016).…”
Section: Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study [37] showed that mHealth apps caused anxiety among breast cancer patients waiting for surgery by sending them multiple reminders. mHealth and medical apps may generate different risks to patients and their safety, and these risks could be even more harmful in complex apps [38]. There are also security concerns regarding patients’ information in mHealth apps, such as risk of data breaches or tampering [39].…”
Section: Perils Of Mhealth In Shared Decision Makingmentioning
confidence: 99%
“…There is currently an interest in standardizing interventions in this area, and there have been attempts to establish criteria to self certify eMedia delivered interventions [5]. Similarly, there is an interest in evaluation of risk assessment of such interventions [6]. Surprisingly, the regulatory agencies have not paid sufficient attention to eMedia-delivered interventions until recently.…”
Section: Introductionmentioning
confidence: 99%